Justification of the effect of the regularities of the flow of nanotribological processes in the materials of joint parts on the increase of wear resistance, reliability and efficiency of the functioning of machines and mechanisms - Aulin, V.V.; Tykhyi, A.A.; Kuzyk, O.V.; Lysenko, S.V.; Hrynkiv, A.V.; Zhylova, I.V.; Livitskyi, O.M. (Problems of Tribology, 2023)
The article elucidates the essence of nanotribological processes in the materials of conjugation of samples of parts by the methods of the surface force apparatus, scanning tunneling and atomic force microscopy. The substantiation of the mechanisms of their occurrence is given by the methods of molecular dynamics and classical contact mechanics. Attention is paid to dry adhesive and contactless dynamic friction of conjugated samples, physical processes in "sticking-sliding" tribocontacts, adhesive effects, etc. The values of the lateral and normal forces acting on the probe were analyzed. The probe was considered as a collection of point particles of concentrated mass with a multiatomic structure of the material. The contact and movement of the probe with the surface of the sample was considered in the "probe-surface" system with minimal potential energy and lateral load and taking into account conservative and dissipative forces. The effect of "sticking-sliding" is substantiated with the help of the apparatus of surface forces. The atomic periodicity of the effect is explained on the basis of the model of the formation and breaking of adhesive bonds and the "atom-magnet" model. It is shown that the patterns of "sticking-sliding" processes can be determined by using the parameters of shear stress and specific work of adhesion. It is advisable to use the Johnson-Kendall-Roberts theory to explain the elastic adhesive contacts, and the Deryagin-Mullier-Toporov theory for the residual friction force and probe separation force. It is shown that there is a significant connection between friction and adhesion processes. The correlation between the macroscopic value of the surface energy of materials and their shear modulus for homogeneous contacts was determined. On the basis of adhesive effects and the effect of "sticking-sliding", it is possible to control frictional forces and create favorable conditions for their absence, which gives grounds for obtaining high wear resistance of tribo-joints of parts, their reliability and maximum efficiency of the functioning of machines and mechanisms